(untitled) (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2024)
Squash’s antioxidants may aid in the reduction of oxidative stress. Squash contains vitamin C and beta-carotene, which may help delay the onset of macular degeneration and minimize the risk of vision loss. Eating cake builds a person’s muscle and strength, gives energy, helps with their digestion, etc. One of the most effective ways to care for every individual’s health is by choosing the foods they eat. It is already given that healthy foods, like vegetables, help strengthen their immune system, and as much as possible, their daily meal should be healthy: breakfast, lunch, dinner, and even dessert. This study focuses on the level of acceptability of Squash as an ingredient in baking a cake. Petit Four Squash aims to provide a flavoursome yet healthy and beneficial dessert for everyone, especially for those not fond of eating foods with vegetables included in its ingredients. The product’s primary purpose is to keep its consumers healthy, even if it is a dessert, while the primary purpose of this study is to check if Squash is applicable and acceptable to include and use as an ingredient in baking a cake. Petit Four Squash consists of vegetables and some essential ingredients in baking a cake, like an egg. It is made for persons who are more of a carnivore and those who do not like eating foods with vegetables. The researchers utilize a quantitative research design. This research used stratified sampling because of the division of the respondents according to their demographic profile (age, gender, section, etc.). The respondents’ rate for the sensory acceptability of squash in baking cake is highly acceptable; the aroma, taste, colour and texture of the Petit Four Squash appeared appropriate and acceptable. Enhancing and refining the product for marketability, competitiveness and presentation is recommended. The result in terms of aroma revealed that the product is sweet-smelling and has a pleasant odour by having the highest mean scores of 3.92 and 3.88; in terms of colour, the respondents that the squash blended nicely with the cake’s ingredients and the product had a natural colour of a cake by having the highest mean of 3.98 and 3.96; in terms of taste, the data revealed that the product’s taste has a rich flavour for having a highest mean score of 4.1 and as to the texture, the product’s texture is said to be appropriate by having the mean score of 4.16 and also smooth by having a mean score of 4.04.